Efektivitas Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Peningkatan Kemampuan Berfikir Kritis Siswa pada Mata Pelajaran Fikih di Madrasah Aliyah Hidayatul Mubtadiin Jati Agung Lampung Selatan - Siti Qoriah; Tamyis Tamyis; Mustaqim Hasan (Departement of Mathematics Education, 2023)
This study aims to evaluate the effectiveness of the Contextual Teaching and Learning (CTL) model of learning in improving students' critical thinking abilities in the subject of Fiqh. The research design used in this study is mixed-methods field research with an experimental design. In this design, there are two groups of students selected through saturation sampling method, namely the experimental group and the control group. The experimental group receives learning using the Contextual Teaching and Learning (CTL) model, while the control group receives learning using the conventional model. Data analysis is performed using a t-test to determine the difference in critical thinking scores between the two groups. The results show a significant improvement in critical thinking abilities of students who receive learning using the Contextual Teaching and Learning (CTL) model compared to students who receive learning using the conventional model (t =2,00 < 8,823 > 2,65). This indicates that the CTL model of learning is effective in improving students' critical thinking abilities in the subject of Fiqh. Therefore, the Contextual Teaching and Learning (CTL) model of learning can be used as an alternative approach to improve students' critical thinking abilities in the subject of Fiqh.